Dampak Pandemi COVID-19 Terhadap Kualitas Pelayanan dan Pengelolaan Keuangan di Rumah Sakit - Indah Mutiara Puspita Sari (Dian Nuswantoro Semarang, 2023)
ABSTRACTThe COVID-19 pandemic has an impact on economic growth, the restrictions imposed also have a negative impact on hospital revenues, resulting in hospitals depending on financing and financial support which can also cause hospital services to be less than optimal. In addition, a heavy workload is also the factor that has the most negative impact on the quality of health services. This literature review starts from topic selection, keyword selection, to searching for journal references from several sources, namely Pubmed and Google Schoolar. The keywords used are services quality impact, economy impact, hospital, during the COVID-19 pandemic. Based on the search results, there were 276 articles which were then selected for up to 6 articles that were included in the discussion. The results of this study are the COVID-19 pandemic has an impact on the economy and operations of the country and the health care system as well as the quality of services in hospitals. The decrease in visitors resulted in hospitals cutting revenue from services so that it could disrupt patient care. The pressure that occurred and the isolation because many health workers were exposed to Covid-19 also caused the quality of service at the hospital to deteriorate.Keyword : Services Quality Impact, Economy Impact, Hospital, COVID-19 Pandemic